The Effect of Profitability, Leverage, and Free Cash Flow on Dividend Policy (Empirical Study of Consumer Goods Companies Listed on the Indonesia Stock Exchange) - Rahmawati, Indah Rento (Jurnal KIAFE, 2024)
This study examines the effects of profitability, leverage, and free cash flow on dividend policy in consumer goods companies listed on the Indonesia Stock Exchange during the 2017–2021 period. This study employs a quantitative approach using secondary data obtained from annual financial reports published on the official website of the Indonesia Stock Exchange. The sample was selected using purposive sampling, resulting in 21 companies that met the research criteria. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS version 26. The results show that profitability, leverage, and free cash flow simultaneously have a significant effect on dividend policy. Partially, profitability and leverage have positive and significant effects on dividend policy, while free cash flow has a negative and significant effect on dividend policy.